Si Gale-Gale Folklore in the Toba Batak Society: A Study of Continuity and Change - Martozet Martozet; Nurwani Nurwani; Merdy Roy Sunarya Togatorop (Budapest International Research and Critics University, 2021)
The Si Gale-Gale folklore contains exemplary values and education about the character of the Toba Batak king named Raja Rahat who is loved by the people who is fair and wise. The king had a son by the name of Raja Manggale who he loved very much and was the only child. King Manggale died on the battlefield, he heroically fought to defend his ancestral land from invaders. The death of King Manggale inflicted a deep wound on King Rahat. To entertain the king, a wooden statue was made as a representative of King Manggale, who magically can move like a dancing person, because it is believed that the spirit of King Manggale enters the statue with the help of the power of a shaman who is termed guru sibaso. This study aims to describe the continuity and change of this oral tradition in the Toba Batak people in North Sumatra. In order to know this folklore, a research was conducted using qualitative methods through field observations, interviews, documentation, and literature studies. As an oral culture and tradition, the legendary Si Gale-Gale folklore has been passed down from generation to generation throughout the Batak Toba generation which is full of values. It is not known when this tradition emerged, but the Toba Batak people believe that this oral tradition arose before the entry of religion into the Toba Batak area. It is known that the Si Gale-Gale folklore provides educational values and role models for the community about the love for the ancestral land and the important role of boys as the next generation according to the system adopted by the Toba Batak community. In its development, this folklore is not only a story that is passed down from generation to generation, but also becomes a cultural tourism offering and attraction for travelers who visit tourist enclaves in the North Sumatra area such as in the tourist area of Lake Toba, especially in the Tomok and Huta areas. Bolon Simanindo, Samosir Regency. In tourist attractions, The statue of Si Gale-Gale as a representation of King Manggale moves staccato or breaks and moves like a dancing person who is driven by a player (dalang) and is accompanied by typical Toba Batak music gondang sabangun.